PENDAMPINGAN PEMBERDAYAAN MASYARAKAT KELOMPOK WIRAUSAHA PEMULA DI PESANTREN AL HIKMAH BANJARMASIN - Basuki Basuki; Aida Vitria; Rahmi Widyanti; Khuzani Khuzaini (JURNAL PENGABDIAN AL-IKHLAS UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARY, 2023)
Every business that is run both small and large aims to make a profit. To find out the extent of the benefits derived from the business / business that is run requires careful recording. The recording of both business expenses and income must be done carefully so that the analysis and calculation of profit and loss of the business carried out with results that reflect the business potential. Pesantren Al Hikmah sub-district is located in Banjarmasin City, an agricultural area, where most of the population (57%) live in rice fields and most (53%) of them (families) depend their livelihoods / livelihoods from the sea as traditional farmers. So far, there has been an outreach and counseling about designing small businesses by a group of mothers, but it has not provided adequate results. This is due to not doing a good business analysis. Through community service activities it seeks to provide knowledge about how to analyze or calculate the price of a product so that it can benefit the producers.Kata kunci : Business Analysis, Homemade Industry